Pathology of the collaterals of the abdominal aorta - Ormaechea, Carlos A (Cirugía del Uruguay, 1972)
Pathological disease of visceral collaterals of the abomina! aorta are rare but highly serious. They present difficult problems in their diagnosis and therapy. Two predominan! pathological p;ocesses are established: obstructions and aneurisms, with their feared complications, infarction and rupture. Surgeons are called upon to consider these diseases when faced with an acute picture of the abdomen and they are given the guidelines for an early diagnosis and for the use of sorne therapeutical resources. The most frequent topographies of the process are listed in order of importance: hepatic artery,- upper mesenteric artery and splenic artery. Finally experiences in our country are reviewed